Quality of counselling assessed by patients after total knee arthroplasty: A cross-sectional study. (November 2022) - Haapala, Antti-Jussi; Rajala, Mira; Kääriäinen, Maria; Kaakinen, Pirjo; Meriläinen, Merja
Abstract: Patient counselling is a key function in nursing. High-quality counselling promotes adherence to treatment and reduces complications. The purpose of the study was to describe the quality of counselling experienced by total knee arthroplasty patients following surgery. The study was a descriptive cross-sectional study. The data were collected from patients following total knee arthroplasty (N = 60) in 2016 with a modified Quality of Counselling Instrument, and analysed using statistical methods. Over half of the patients (58%) were women and the mean age was 68 years (range 49–84). Over a quarter of patients (28.9%) lived alone, and about two-thirds were overweight (42.1%), or obese (31.6%). After surgery, many patients (88%) experienced moderate pain. Half of patients (52.6%) received a good quality of counselling for the disease and its treatment, and counselling for recovery from treatment (81.6%) was good. Most patients (92.1%) received satisfactory counselling about physical activity. There was a correlation between the disease and its treatment counselling and quality of life (r = −0.553, p = 0.003) and pain (r = −0657, p = 0.000). Interaction during counselling was good (97.4%) and it was implemented in a patient-centred way (89.5%). High-quality counselling implemented in a patient-centred manner can play a part in reducing pain and increasing patients' quality of life.